Evaluation of Decision Making on Using Online Media in the D'Amerta Berniaga Bandung Business Group - Alam Avrianto; Ira Murwenie; Rahmina Puspa AR; Dwirani Fauzi L; Abdul Fatah H (Universitas Insan Cendekia Mandiri, 2023)
An organization/company cannot be separated from decision-making. Intuitive decision-making is highly discouraged if it is not from a reliable source because the level of deviation that occurs can be very large. Therefore, we need a reliable basis for making a decision. The D'Amerta Berniaga business group does not use online media to carry out its business. This has resulted in the underdevelopment of the business being carried out, given the increasingly fierce business competition at this time. However, the decision to use online media is very difficult considering that business owners are housewives and sole implementers in their businesses. This resulted in an increase in workload and a very large amount of time to use online media, causing doubts about the decisions to be taken. Therefore, training on the use of online media was carried out in an effort to overcome this problem. The existence of training makes business owners interested in using online media. The business owner's decision to use online media needs to be evaluated to determine the accuracy of the decisions taken. This study aims to see whether the decisions taken by business owners, namely using online media, are appropriate and able to contribute to their business. The method used is a quantitative method with a descriptive approach. Measurements were made based on the total population of 30 respondents by pretest-posttest. Based on the test results with the paired t-test, it can be seen that the decisions taken, namely using online media, have a significant influence on existing businesses.